Hubungan Kepatuhan Diet dengan Kualitas Hidup pada Penderita Diabetes Mellitus Tipe 2 di Banda Aceh - Phoenna, Cut Putri; Maulina, Maulina; Ridwan, Arfiza (Journal of Bionursing, 2024)
Background: Patients with type 2 diabetes mellitus tend to have problems with their diet. Non-compliance in maintaining a diet will affect the quality of life, that lead to worsening the prognosis of the disease. Therefore, it is important for them to adhere to a diet by paying attention to the right type, amount, and schedule to improve the quality of life. Objectives: The purpose of this study was to determine the relationship between diet compliance and quality of life of patients with Type 2 Diabetes Mellitus in Banda Aceh city. Methods: This study used quantitative methods with a correlative descriptive design and a cross-sectional study approach. The population is Type 2 Diabetes Mellitus Patients who visited the Ulee Kareng Health Center from May to July 2023 as many as 145 people. A sample size with 107 respondents using Slovin formula. The sampling technique used to obtain the sample is proportional sampling. Data collection tools using the Dietary Adherence Questionnaire and The World Health Organization Quality Of Life (WHOQOL)-BREF Questionnaire. Results: Analysis of research results using Spearman's rank test. The results showed that there was a relationship in a positive direction between dietary compliance and quality of life patients with type 2 diabetes mellitus (p < 0.05). Conclusion: It can be concluded that dietary compliance is related to the quality of life of patients with Type 2 Diabetes Mellitus. It is expected that the health care nurse monitor and evaluate patient related to diet compliance so that the quality of life becomes better.